Elevated serum CA 19-9 levels in dermoid cyst: a predictor of ovarian torsion and tissue necrosis? - Bhatia, Ruby; Kaur, Simmanjit; Mor, Sunita; Kaur, Naazbir; Gupta, Ritika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Dermoid cyst (mature cystic teratoma) with well differentiated derivatives of all the three-germ cell layer is a benign tumour with ovaries being the commonest site. Dermoid cyst accounts for more than half of ovarian tumours in girls below 20 years of age. 80% of dermoid cyst are seen in reproductive age group between 20-40 years. Size of dermoid cyst usually varies between 5-10 cm and it may be bilateral in 10% of cases. Malignant transformation is very rare occurrence only in 1-3% cases, however torsion may occur in 15% of dermoid cyst. Carbohydrate antigen or cancer antigen 19-9 is usually raised in gastrointestinal tumours, pancreatic malignancy, pseudocyst of pancreas. However, it may be raised in some other malignancies and benign condition like torsion of dermoid cyst. Authors report an unusual case of torsion large dermoid cyst with tissue necrosis along with significantly elevates levels of serum CA 19-9. A 30-year-old P1L1 female presented with chief complaint of heaviness and pain lower abdomen and loss of five kilogram weight for last three months. A provisional diagnosis of dermoid was made. Serum CA 19-9 level were 1126 IU significantly raised. An exploratory laparotomy done under regional anaesthesia. A large demoid cyst 12*10 cm with torsion and areas of gangrene in ovarian tissue was seen replacing left ovary. Large and small intestine, stomach, pancreas were explored to rule out any pathology. Histopathology confirmed diagnosis of mature cystic teratoma. There was significant fall in serum Ca 19-9 levels to 247 U/ml two weeks after surgery and levels returned to normal limit six weeks after surgery.